Clinical and Epidemiological Characteristics of Multiple Sclerosis in a Peruvian Cohort: A Retrospective Study Across Three Lima Hospitals - Ana Cruz Cruz; Julio Perez-Villegas; Eduardo Alvarado; Edward Smith; Ivan Dueñas-Pacheco (Neurology International, 2026)
Background/Objectives: To describe the demographic, clinical, and epidemiological characteristics of a cohort of patients diagnosed with Multiple Sclerosis (MS) in Lima, Peru. Methods: A descriptive, retrospective cohort study conducted across three major hospitals in Lima. We included adult patients diagnosed with MS in any of its clinical phenotypes—Clinically Isolated Syndrome (CIS), Relapsing-Remitting MS (RRMS), Secondary Progressive MS (SPMS), and Primary Progressive MS (PPMS)—who were followed between 2007 and 2017. Results: A total of 103 patients were identified. The majority were women (58.3%), with a median age at onset of 38.4 years (Interquartile Range [IQR]: 28.9–46.5). The most common clinical phenotype at onset was RRMS (90.3%), which remained the most prevalent phenotype at the current evaluation (79.6%). Twelve patients (12.9%) progressed from RRMS to SPMS by their last control visit. The most frequent symptoms at onset were limb weakness (72.8%), sensory symptoms (72.8%), and blurred vision (42.0%). At the last evaluation, the most frequent symptoms were limb weakness (78.6%), sensory symptoms (71.8%), and spasticity (40.2%). The most common initial treatment was interferon-beta (44.7%), while two patients (1.9%) initiated therapy with a highly effective disease-modifying drug (DMD), Ocrelizumab. The most recent treatment reported remained interferon-beta (33.9%), but 12 patients (11.7%) were currently receiving Ocrelizumab. Conclusions: This study describes clinical characteristics at onset and during follow-up that are largely similar to those reported in international series. However, we found no evidence of improved disease evolution, a finding potentially attributable to the heterogeneity of treatment and management strategies employed across the cohort.